2020
DOI: 10.1055/a-1119-6327
|View full text |Cite
|
Sign up to set email alerts
|

Confocal laser endomicroscopy detects colonic inflammation in patients with irritable bowel syndrome: a prospective study

Abstract: Background and aims Irritable bowel syndrome (IBS) is considered to be a functional disease, but recent data indicate measurable organic alterations. We aimed to determine the presence of colorectal mucosa microinflammation in vivo via probe-confocal laser endomicroscopy (pCLE) and histological evaluation in IBS patients. Methods This was a prospective, controlled, nonrandomized single-blind diagnostic trial performed in a tertiary institution. pCLE images and targeted biopsy of each colon segment ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…Small intestinal barrier function has also received considerable attention as a potential pathomechanisms in irritable bowel syndrome (IBS) (2), and this in fact predates similar hypotheses with regards to FD. More interestingly, other studies in patients with IBS using confocal laser endomicroscopy have demonstrated largely similar barrier defects in the distal duodenum (3), terminal ileum (4) and colon (5) to those observed in the Nojkov study in FD patients.…”
supporting
confidence: 55%
“…Small intestinal barrier function has also received considerable attention as a potential pathomechanisms in irritable bowel syndrome (IBS) (2), and this in fact predates similar hypotheses with regards to FD. More interestingly, other studies in patients with IBS using confocal laser endomicroscopy have demonstrated largely similar barrier defects in the distal duodenum (3), terminal ileum (4) and colon (5) to those observed in the Nojkov study in FD patients.…”
supporting
confidence: 55%
“…While similar studies in humans are lacking, it has been reported that neutrophil counts in colonic biopsies of patients with IBS are significantly increased compared to control [39], which may in turn result in increased myeloperoxidase levels, for example, in the colon tissue. Additionally, a very recent study utilising confocal laser endomicroscopy, reported that patients with IBS have a six-fold higher prevalence of colorectal mucosa micro-inflammation than healthy controls [193]. Considering that inflammation and oxidative stress are linked, often occurring in tandem, it is likely that local effects of oxidative damage/stress are implicated in IBS-related gastrointestinal symptomology.…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%
“…The shape of probe-based CLE (pCLE) and needle-based CLE makes possible to pass through most kinds of endoscopic channels, which greatly increases the scope usage. Currently, this tech-nique is used in diagnosis in various digestive organs, including esophagus, stomach, duodenum, colon-rectum, biliary and pancreatic duct, pancreas, and liver [14][15][16][17][18][19][20][21][22][23][24][25]. Its accuracy in diagnosis of Barrett's esophagus, pancreatic cystic degeneration, bile duct stricture, and other diseases is comparable to the histological diagnosis.…”
Section: Confocal Laser Endomicroscopymentioning
confidence: 99%